Facial fractures at a tertiary health care facility vis a vis time of presentation: a pilot study - Munjal, Manish; Kanotra, Sonika; Munjal, Shubham; Chopra, Parth; Saggar, Tulika; Chopra, Hemant; Uppal, Sanjeev (International Surgery Journal, 2022)
Background: Facial trauma patients were analyzed to determine the time of presentation at the trauma unit following, fractures of the naso-orbital and maxilla-mandibular region. Methods: This prospective study was conducted at Dayanand medical college and hospital, Ludhiana, Punjab, for a period of two years from January 2015 to June 2017. 61 patients admitted in the maxillofacial trauma unit were analyzed. Results: The males outnumbered the females in the ratio of 5: 1. The maximum numbers of patients 33 patients (54%) were seen in the age group 21-30 years and minimum at extremes of age. Vehicular trauma was the predominant etiology, noted in 44 cases (72.13%). Most of the patients, i.e., 85 cases (95.1%) of the fractures, were seen within 24 hours of sustaining trauma. Only 2 cases (2.4%) of fracture were admitted on the second day. The only case of orbital blow out fracture reported 41⁄2 months after injury. Conclusions: Most (93.4%) of the patients with facial fractures presented on the same day of injury. 2 cases of zygomatic fracture presented on the 2nd day and one on the 3rd day.